Determination of thyroglobulin levels by radioimmunoassay method in anti thyroglobulin positive differentiated thyroid patients: One center clinical experience - Ucar, Burcu; Sen, Melis; Acar, Tayfun; Demirkol, Mehmet Onur (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
It is very crucial to determine Tg accurately and precisely in thyroid cancer cases. Although there are many studies on the detection of Tg in thyroid cases in the literature, there are no sufficient clinical studies examining many cases with different features by using RIA methodology. Here, a radiometric and chromatographic method has been studied for the first time to eliminate the interference from anti-Tg positive patients. In this paper, radioimmunoassay (RIA) and immunoradiometric (IRMA) techniques were used for the analysis of 302 sera collected from patients for Tg and TgAb quantification. By the RIA technique, a reliable result was obtained by calculating the real Tg value quantitatively in 41 patients showing TgAb positivity out of 208 patients. Our findings show that the RIA assay is the most suitable approach for detection of changeable (low or undetectable) Tg value and metastases detected by post-therapeutic imaging in early-stage DTC cases showing preoperative and postoperative TgAb positivity. The new immunoradiometric method allows the real (%) Tg value to be reached in a part of TgAb-positive DTC. Even if TgAb positive in the metastatic and nonmetastatic DTC patient group. This allows the accurate clinical follow-up of patients.
Keywords: Thyroglobulin; Thyroglobulin antibodies; Thyroid cancer; Radioimmunoassay; I-125-tracer; SERUM THYROGLOBULIN; CANCER PATIENTS; FOLLOW-UP; IN-VITRO; AUTOANTIBODIES; ANTIBODIES; TG; CARCINOMA; IMPACT; ASSAYS; Chemistry; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging